Effects of an 8-Week Plyometric Depth Jump Training Program on Badminton Smash Accuracy and Lower Body Power in Amateur Athletes: A Randomized Controlled Trial - Vickery, Tina; Azevedo , Eugénia; Németh, Zsolt; Frazer , Mellissa (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2025)
Purpose of The Study. To investigate the effects of an 8-week plyometric depth jump training program on badminton smash accuracy in amateur athletes and examine the relationship between lower body power development and overhead striking precision. Material and methods. Twenty-four amateur badminton athletes (14 males, 10 females; age: 19-25 years) were randomly assigned to experimental (n=12) and control (n=12) groups. The experimental group performed progressive plyometric depth jump training three times per week in addition to regular badminton practice, while the control group maintained only regular practice. Platform heights progressed from 40-55 cm over 8 weeks. Smash accuracy, vertical jump performance, ground contact time, and movement efficiency were assessed pre- and post-intervention. Results. The experimental group demonstrated significant improvements in smash accuracy (29.6%, p < 0.001, d = 2.21), vertical jump height (13.2%, p < 0.001, d = 1.78), and ground contact time (15.7% reduction, p < 0.001). Strong correlations were observed between vertical jump improvements and accuracy enhancements (r = 0.76, p < 0.001). The control group showed minimal changes (4.4% improvement in accuracy, p = 0.089). No significant gender differences were found in adaptation rates (p = 0.085). Conclusions. An 8-week plyometric depth jump training program significantly improves badminton smash accuracy in amateur athletes, suggesting that enhanced lower body power development directly contributes to improved striking precision. The findings support integrating structured plyometric training into regular badminton practice for technical skill enhancement.